Growth Pattern, Biochemical and Physiological Characteristics to Determine Harvesting Time of Big White Ginger Rhizome Seeds - Rusmin, Devi; Suhartanto, M.R; Ilyas, S.; Manohara, Dyah; Widajati, E. (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
The use of young seed rhizomes became one of the obstacles in large white ginger (JPB) cultivation. Young ginger rhizomes rapidly shrank and decrease their viability. The experiment was aimed to study growth patterns, biochemical changes, and physiology of ginger plants to produce good quality rhizome seeds. JPB rhizome seeds used were 9 months old, have been stored for 2 weeks after harvest, weighed 30-40 g with 2-3 buds, healthy, and given seed treatment. The rhizomes were planted in growth medium in polybags (60 cm x 60 cm). The study was conducted by direct observation, repeated 4 times, consisting of 50 plants per replication. Observations were made on the plant growth patterns (plant height, stem length, tillers number, leaves number); rhizome development (fresh weight, branch rhizomes number, moisture content, and dry weight during growth); starch and hormonal content (IAA, gibberellin, ABA and cytokinin) of the rhizomes; and viability of rhizome seeds (growth rate, seed height, and dry weight). The results showed that the rhizomes of the 7-month-old ginger after planting (MAP) has entered the ripening phase, the rhizome morphology was optimal, and the starch content was not different from the rhizome seeds at 8 and 9 MAP. In addition, physiologically, the rhizome's growth potential was maximal (100%), growth rate (4.3% etmal-1), and seed height (33.8 cm) were better than 8 MAP (80%, 2.9% etmal-1, 33.7 cm) and 9 MAP (70%, 2.3% etmal-1, 29.4 cm). This study indicated that ginger rhizomes harvested from 7 months old plants can be used for seeds.